Hadith #2354 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Asim al-Ahwal عاصم الأحول; Hafsa bint Sirin حفصة بنت سيرين; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
I and Masruq entered upon ‘Aishah and we said: Mother of believers, there are two persons from the Companions of the Muhammad (ﷺ). One of them hastens to break the fast and hastens to pray while the other delays to break the fast and delays praying. She asked: Which of them hastens to break the fast and hasten to pray ? We replied: ‘Abd Allah (b. Mas’ud). She said: Thus did the Messenger of Allah (ﷺ) do.
Grade: Sahih

Hadith #2838 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A boy is in pledge for his Aqiqah, Sacrifice is made for him on the seventh day, his head is shaved and he is given name. Abu Dawud said: The word wa yusamma is sounder as narrated by Salam b. Abi Muti’ from Qatadah, and narrated by Iyas b. Daghfal and Ash’ath from al-Hassan who narrated wa yusamma (and he is given a name).
Grade: Sahih

Hadith #3126 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A child was born to me at night and I named him Ibrahim after his. He then narrated the rest of the tradition. Anas said: I saw it at the point of the death before the Messenger of Allah (ﷺ). Tears began to fall from the eyes of the Messenger of Allah (ﷺ). He said: The eye weeps and the heart grieves, but we say only what our Lord is pleased with, and we are grieved for you, Ibrahim.
Grade: Sahih

Hadith #3143 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
We braided her hair in three plaits.
Grade: Sahih

Hadith #3144 - Sunan Abi Dawud - Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Hafsa bint Sirin حفصة بنت سيرين; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
we braided her hair in three plaits and placed them behind her back, one plait of the front side and the two side plaits.
Grade: Sahih

Hadith #3166 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Prophet (ﷺ) said: If any Muslim dies and three rows of Muslims pray over him, it will assure him (of Paradise). When Malik considered those who accompanied a bier to be a few, he divided them into three rows in accordance with this tradition.
Grade: Da'if